Warmer Is Deadlier: A Meta‐Analysis Reveals Increasing Temperatures Accentuate Disease Effects on Fisheries Hosts - Megan M. Tomamichel; Kaitlyn I. Lowe; Kaylee M. H. Arnold; Marc. E. Frischer; Brian J. Irwin; Craig W. Osenberg; Richard J. Hall; James E. Byers (Ecology Letters, 2025)
Rapid warming could drastically alter host–parasite relationships, which is especially important for fisheries crucial to human nutrition and economic livelihoods, yet we lack a synthetic understanding of how warming influences parasite‐induced mortality in these systems. We conducted a meta‐analysis using 266 effect sizes from 52 empirical papers on harvested aquatic species and determined the relationship between parasite‐induced host mortality and temperature and how this relationship was altered by host, parasite, and study design traits. Overall, higher temperatures increased parasite‐induced host mortality; however, the magnitude of this relationship varied. Hosts from the order Salmoniformes experienced a greater increase in parasite‐induced mortality with temperature than the average response to temperature across fish orders. Opportunistic parasites were associated with a greater increase in infected host mortality with temperature than the average across parasite strategies, while bacterial parasites were associated with lower infected host mortality as temperature increased than the average across parasite types. Thus, parasites will generally increase host mortality as the environment warms; however, this effect will vary among systems.